2018
DOI: 10.1039/c7ta11190h
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal-like optoelectronic-properties of MAPbI3 perovskite polycrystalline thin films

Abstract: Our understanding of the crystallization process of hybrid halide perovskites has propelled the efficiency of state-of-the-art photovoltaic devices to over 22%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 46 publications
(51 reference statements)
7
57
0
Order By: Relevance
“…This prediction corresponds well with the prevalence of experimental studies of MAPbI 3 in the literature, in which it has been considered one of the best-performing compositions. 3,25,26 In addition, experiments by Choi et al have shown the particular efficacy of the THTO additive to dissolve Pb, corroborating these BO-guided/DFT-driven predictions. 27 The caliber of the prediction for the mixed halides case is more difficult to evaluate since the experimental community has not yet decided on an optimal composition, probably because the number of options is overwhelming.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This prediction corresponds well with the prevalence of experimental studies of MAPbI 3 in the literature, in which it has been considered one of the best-performing compositions. 3,25,26 In addition, experiments by Choi et al have shown the particular efficacy of the THTO additive to dissolve Pb, corroborating these BO-guided/DFT-driven predictions. 27 The caliber of the prediction for the mixed halides case is more difficult to evaluate since the experimental community has not yet decided on an optimal composition, probably because the number of options is overwhelming.…”
Section: Discussionsupporting
confidence: 53%
“…Once more, we find that THTO is a superior additive for dissolving ABX 3 . 26,27 It is important to note that the Bayesian search produces a ranked list in which a number of candidates may produce closeto-optimal suggestions that meet the target value within the uncertainty of the methodology. That is true in this case, where four compositions are the highest performers with binding energies within 0.84 kJ/mol (0.2 kcal/mol) of each other, making them essentially inseparable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that high defect densities in the material due to the not densely-packed nanocrystalline MASI thin film morphologies are responsible for the low photovoltaic efficiencies. Assuming internal quantum efficiencies near unity as observed in MAPbI 3 -based solar cells, possible current densities based on our thin-film absorption are around 9 mA cm −2 (see SI figure 1(d)) [46]. In combination with a voltage of 1 V, which is defined by the energy level alignment of the HTL and ETLs used in this work, device efficiencies of around 6% are probable.…”
Section: Resultsmentioning
confidence: 63%
“…This hysteresis could be reduced by scraping the film from the substrate and instead measuring randomly oriented powder samples. Generally, increasing grain sizes in MAPbI 3 films has resulted in improvements in critical performance parameters, such as an increase in carrier mobility and charge collection efficiency, [33,34] along with smaller bandgaps, longer lifetimes, Grain size in polycrystalline halide perovskite films is known to have an impact on the optoelectronic properties of the films, but its influence on their soft structural properties and phase transitions is unclear. Unless understood and mitigated, such hysteretic changes at low temperature may limit the use of perovskite solar cells in some specific applications, for example, aerospace applications, which require operation at extremely low temperatures [28] (<200 K).…”
mentioning
confidence: 99%